Phase equilibrium and kinetic studies of choline chloride-based deep eutectic solvents in water system for the inhibition of methane gas hydrate formation - Aliyu Adebayo Sulaimon; Ali Qasim; Mohamad Athif; Asiah Nusaibah Masri; Pearl Isabellah Murungi; Aneel Jordan Atthi Tasan Singh (Journal of Ionic Liquids)
Gas hydrates in subsea pipelines can lead to blockages, potentially causing explosions, and Deep Eutectic Solvents (DESs) offer an alternative to traditional chemical inhibitors or can minimize their usage when mixed with other chemicals. The thermodynamic hydrate inhibition (THI) and kinetic hydrate inhibition (KHI) behavior of two DESs i.e., choline chloride (ChCl) solution with glycerol and ethylene glycol are investigated using Micro Differential Scanning Calorimetry (μ-DSC). The DES-in-water systems were prepared by diluting the prepared DES in water. The difference between water-in-DES and DES-in-water systems is based on the extent of dilution. For DES-in-water systems, the water is in higher concentration and DES is a minor component. Whereas, water-in-DES systems involve adding a small amount of water to a DES. This can disrupt the hydrogen bonding network within the DES, leading to changes in its physical and chemical properties. The concentration of the DES solution was 10 and 15 wt% and the study was performed in-between the pressure range of 6.32–13.27 MPa while the Hydrate-Liquid-Vapor-Equilibrium (HLVE) temperature lies between the range of 281.4–290 .1K. Both compounds acted as thermodynamic and kinetic hydrate inhibitors for methane gas hydrates. HLVE was calculated for five pressure values. THI results show that the average depression temperature (ADT) of ChCl: Ethylene glycol is 1.47 K which is higher than the ADT achieved by ChCl: glycerol of 0.50 K at 10 wt%. Also, regarding kinetic hydrate inhibition, ChCl: Ethylene glycol showed better performance than ChCl: glycerol. The highest induction time attained by ChCl: Ethylene glycol is 1.5 h at 14.1 bar while for ChCl: glycerol, it is 1.2 h at the same pressure. Thermodynamic hydrate modeling for methane hydrates was also performed using the Dickens and Quinby-Hunt model. It showed an overall Mean Absolute error (MAE) value of 0.26 K while for the ChCl: Ethylene Glycol system, the MAE value is 0.32 K. The R2 value was higher than 0.90 for both systems, proving the model's good fit. DESs have the potential to be applied in practical flow assurance applications due to their environmentally benign properties. The work is novel as it investigates the use of DESs for methane hydrate inhibition at high pressure along with the thermodynamic modeling.